The Exploration and Governance of Privilege Thought and Privilege Phenomenon - Xu, Qianyun (Journal of Theory and Practice of Contemporary Education, 2023)
Privilege thought and phenomenon are breeding grounds for corruption, and the governance of privilege phenomenon has become an important issue for the CPC. This article first analyzes and explores the root causes of the idea and phenomenon of privilege, and analyzes several forms of expression of the current idea of privilege, and finally implements how to effectively control the phenomenon of privilege, aiming to root out the soil for the spread of the idea and phenomenon of privilege from the source, so that the CPC will always receive the support of the people and remain invincible.